Graduate employability in Sabah's agriculture sector: perception and expectation of employers and graduates - Wan Hurani Osman; Rosmah Murdad (Scientific Journal, 2020)
Graduate Employability and unemployment is a common problem in most developing countries, including Malaysia. Among the factors that that contribute to unemployablity are lack of experience, communication skills, soft skills and industry-academia gap of mismatching graduates' skills with industrial demands.In view of this, it is discovered that very few studies show graduate employability skills among agricultural graduates in Malaysia, especially in Sabah. Therefore, this study aims to identify the expectations and the important criteria in terms of skills, knowledge, or personal qualities of agricultural graduates from the Faculty of Sustainable Agriculture according to employers‟ views and to compare with graduates‟ pespective in Sabah. Besides, this research intended to identify the graduates level of awareness regarding the employers‟ expectation. This study employs a mixed approach in which interview sessions and open-ended surveys were conducted with seven government and private employers in agriculture-based companies in Sabah. A total of 77 FSSA graduates in 2019 represent new agricultural employees.Data were collected from two different sets of questionnaires. A direct comparison was made by applying the same scoring method to both employers and graduates. Overall this study shows an inverse relationship between the expectation of employers and graduates perceptions. Therefore, cooperation between institutions and industry is crucial to reduce this gap. This effort can be done by holding a round table discussion, industrial talk at the university and sabbatical training of lecturers to agricultural-related companies. The industry can also be involved in the process of establishing new programs and curriculum revisions. It is hoped that this effort will produce graduates that are matched with the needs of the industry. Hence will increase graduate employability.